A review on computer technology applications in fraud detection and prevention / Rafidah Zainal, Ayub Md Som and Nafsiah Mohamed. - Zainal, Rafidah; Md Som, Ayub; Mohamed, Nafsiah (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
Since the advancement in computer technology, fraud has become one of the high risk crimes in the world which needs urgent detection and prevention at early stage. Nowadays, different kinds of fraud exist in commercial areas namely; credit card, healthcare insurance, online reviews, telecommunications, automobile, etc. Fraud can also happen internally and externally in an organisation. In internal fraud an employee commits it individually, whereas the external fraud involves a wide range of schemes including a third party. Therefore, a detection and prevention mechanism system in the form of computer software is essential in preventing fraud so as to curb further financial losses. The aim of this paper is to critically review the use of computer technology to detect and prevent fraud in selected areas. Recent computer platforms used as a tool to develop fraud detection and prevention system are namely; spreadsheets, big data, forensic analytics, text analytics and expert systems. Based on the review, expert systems have been found to be the best option used as a future tool to curb fraud. The opportunities from this review may allow others to explore more on the technology implemented so as to improve fraud detection and prevention in the future.